Characterization of strains containing mutations in the contiguous flaF, flbT, or flbA-flaG transcription unit and identification of a novel fla phenotype in Caulobacter crescentus. - Schoenlein, P V (1989)
During the Caulobacter crescentus cell cycle, flagellin synthesis and filament assembly are temporally controlled events which require the products encoded by the contiguous flaF, flbT, and flbA-flaG transcription units (P.V. Schoenlein, L.S. Gallman, and B. Ely, J. Bacteriol. 171:000-000, 1989). To better define the functions of these genes, immunoprecipitation studies, Western blot (immunoblot) analyses, and electron microscopic analyses characterized flagellin synthesis and assembly in mutant and merodiploid strains. Mutations in the flaF or flbA-flaG transcription unit resulted in reduced synthesis of the 25- and 27-kilodalton (kDa) flagellins. In contrast, mutations in flbT resulted in overproduction of these flagellins. The FlbT phenotype is unique, since all other identified C. crescentus fla mutations cause a reduction in the levels of the 25- and 27-kDa flagellins. Furthermore, the flbT mutant showed a chemotaxis deficiency even though it was motile. Thus, the flbT gene product appears to be involved in the regulation of both flagellin synthesis and chemotactic function. Mutations in the flbT and flbA-flaG transcription units also resulted in the production of a 22-kDa flagellin species that is not normally detected in wild-type cells. This flagellin species was not detected in the flbT filaments. Furthermore, the 22-kDa flagellin was no longer detected in flbA pseudorevertants that assembled functional filaments. Thus, the 22-kDa flagellin does not appear to be assembled into filaments. Since many of the flbT filaments are shorter than wild-type filaments, we discuss the possibility that the 22-kDa flagellin species may adversely affect flagellin assembly in this mutant.